Developing Entrepreneurial Creativity through Creative Thinking Skills: Qualitative Study on Halal Industry SMEs in Pesantren - Eti Nurhayati; Salam Dz, Abdus (Program Pascasarjana, Universitas Islam Bunga Bangsa Cirebon, 2025)
The halal industry in Indonesia is experiencing significant growth, with an increasing number of business actors involved, including within the pesantren environment. Pesantren have great potential to develop entrepreneurship through creative thinking skills. However, there are challenges in optimizing entrepreneurial creativity among santri. This study aims to explore the influence of creative thinking skills in developing entrepreneurial creativity in halal industry SMEs based in Bobos Cirebon Islamic boarding schools. This research provides novelty by examining the relationship between creative thinking skills and entrepreneurship development in pesantren within the context of the halal industry. The method used is qualitative research with a case study approach, involving in-depth interviews with SME managers and students involved in the halal industry. The results show that creative thinking skills play a crucial role in driving product innovation, solving business problems, and creating new opportunities within halal industry SMEs. Additionally, social support factors and entrepreneurship training in pesantren also strengthen entrepreneurial creativity. In conclusion, the ability to think creatively can be key to developing entrepreneurial creativity in pesantren and increasing the competitiveness of SMEs in the halal industry sector. The social implication of this study is the importance of integrating creativity and entrepreneurship training into the pesantren curriculum to produce creative entrepreneurs who can contribute to the development of the halal industry.